"Wiraku Suci": a children's app for learning hygiene practices / Aznoora Osmana and Nurul Husniyah Mohd Azman - Osman, Aznoora; Mohd Azman, Nurul Husniyah (Universiti Teknologi MARA, Perlis, 2021)
Hygiene care is a basic human need, but very essential practice that must be taught since childhood. Personal hygiene involves making sure body parts are clean to avoid from health issues caused by poor cleanliness. Parents ultimately bear the responsibility to teach their children about cleanliness, and normally this is done by showing and practising hygiene care themselves. Nevertheless, it is not that easy to educate personal hygiene care to them, especially in the ages of four to six years old, because they are actively playing and exploring their environments. To aid parents, mobile learning app could be employed because hygiene habits can be shown via more engaging ways such as through pictures and video clips of personal hygiene care, simple drag and drop games, and pictorial quiz. In this study, a mobile learning app with game-based approach has been developed by following the software development life cycle Spiral model. During evaluation phase, a heuristic evaluation with five Computer Science lecturers was conducted to examine the usability of the app. Results from the evaluation were used as guidance to refine and improvise the app so that they will be usable and enjoyable for children.